2021
DOI: 10.3390/cancers13246309
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Molecular Profiling of Human Papillomavirus Associated Head and Neck Squamous Cell Carcinoma Treated with Immune Checkpoint Blockade Compared to Survival Outcomes

Abstract: Recurrent/metastatic (R/M) head and neck squamous cell carcinoma (HNSCC) patients overall have a poor prognosis. However, human papillomavirus (HPV)-associated R/M oropharyngeal squamous cell carcinoma (OPSCC) is associated with a better prognosis compared to HPV−negative disease. Immune checkpoint blockade (ICB) is the standard of care for R/M HNSCC. However, whether HPV and its surrogate marker, p16, portend an improved response to ICB remains controversial. We queried the Caris Life Sciences CODEai database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Instead, a comprehensive NGS panel may be effective in assessing a broad spectrum of genetic alterations in TSCCs. Recent studies on oropharyngeal cancers using NGS platforms have reported high TP53 (33–55.4%) and PIK3CA (26.8%) mutation frequencies, comparable to those observed in our study [ 41 , 42 , 46 ]. Notably, 58.1% of tonsil cancers harbored candidate target mutations in 14 genes ( ALK , ATM , EGFR , ERBB2 , FGFR3 , FLT3 , IDH1 , IDH2 , KIT , KRAS , MET , PDGFRA , PIK3CA , and SMARCB1 ) with level 1 evidence in OncoKB™, which could be implicated in targeted therapies in the future.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Instead, a comprehensive NGS panel may be effective in assessing a broad spectrum of genetic alterations in TSCCs. Recent studies on oropharyngeal cancers using NGS platforms have reported high TP53 (33–55.4%) and PIK3CA (26.8%) mutation frequencies, comparable to those observed in our study [ 41 , 42 , 46 ]. Notably, 58.1% of tonsil cancers harbored candidate target mutations in 14 genes ( ALK , ATM , EGFR , ERBB2 , FGFR3 , FLT3 , IDH1 , IDH2 , KIT , KRAS , MET , PDGFRA , PIK3CA , and SMARCB1 ) with level 1 evidence in OncoKB™, which could be implicated in targeted therapies in the future.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of specific clinicodemographic features concerned with PIK3CA mutation has been suggested in oropharyngeal cancers [ 27 ], although some studies have characterized rare patients with decreased exposure to tobacco or HPV-positivity by the clinicopathological features of PIK3CA mutation [ 16 , 40 ]. Previous studies have reported that TP53 mutations are common in HPV-negative tumors, while PIK3CA mutations are frequent in HPV-positive cancers [ 27 , 40 , 41 ]. Recent NGS-based studies identified TP53 (9.3–25.0% vs. 63.8–85.7%) and PIK3CA (20.1–21.4% vs. 6.4–32.1%) in HPV-positive and -negative oropharyngeal SCCs [ 42 ], respectively, indicating that although the total number of TP53 and PIK3CA mutations may differ depending on the HPV status, these may still be relatively prevalent [ 16 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, HPV-positive HNSCCs exhibited a relatively low mutational burden (2.28 mutations per Mb vs. 4.83 mutations per Mb in HPV-negative cases) ( 32 ), a high proliferative index, a frequent alteration in the PIK3CA pathway, compared to HPV-negative HNSCCs ( 35 ). A current study reported that the most frequent mutation exhibited in an OPSCC cohort with 948 subjects was TP53 (33%), followed by PIK3CA (17%) and KMT2D (10.6%); and TP53 was more commonly mutated in the HPV-negative group (mutation rate: 49% vs. 10%, P < 0.0005) ( 36 ).…”
Section: Hpv and Opsccmentioning
confidence: 94%
“…Thus, a persistent HPV infection makes cancers much more likely to develop and progress [ 8 ]. Compared with HPV- HNSCC, HPV+ HNSCC has been shown to exhibit a better prognosis and sensitivity to radiotherapy and chemotherapy [ 9 ], perform a lower mutational burden, expressed a wild TP53 [ 10 , 11 ], have more tumor-infiltrating lymphocytes [ 12 ] as well as the less hypoxic [ 13 ], however, why HPV+ HNSCC performs better prognosis and the sensitivity of radiotherapy and chemotherapy still remains unclear.…”
Section: Introductionmentioning
confidence: 99%